Is there 'discretionary space' in rank-based police constabularies for graduate constables to think critically and make autonomous decisions?. (June 2022) - McCanney, John; Taylor, Julie C; Bates, Elizabeth A
The Police Education and Qualification Framework (PEFQ) mandated that from 2020 police recruits must be educated to degree level. This change has generated much debate around the relationship between academia and the police. There has been less discussion about parallel organisational change. To explore the opportunities for graduate officers to find the 'discretionary space' to employ the skills associated with university study, 234 police constables were surveyed. Analysis revealed that officers faced barriers to decision-making from bureaucratic and managerial procedures. Findings suggest that police organisations may need to make changes structurally and procedurally to benefit from a graduate workforce.